Globalization, Oral Performance, and African Traditional Poetry - Na'Allah, Abdul-Rasheed (Springer International Publishing, 2018)
This book discusses globalization trends and influences on traditional African oral literary performance and the direction that Ilorin oral art is forced to take by the changes of the twenty-first century electronic age. It seeks a new definition of contemporary African bourgeois in terms of their global reach, imitation of foreign forms, and collaboration with the owners of primary agencies. Additionally, it makes a case that African global lords or new bourgeoisie who are largely products of the new global capital and multinational corporations' socio-political and cultural influences fashion their tastes after Western cultures as portrayed in the digital realm. Abdul-Rasheed Na'Allah is Vice-Chancellor, Chief Executive Officer, and Professor of English and Comparative Literature at Kwara State University, Nigeria. He is co-author of Introduction to African Oral Literature and Performance (2005), and author of Africanity, Islamicity and Performativity: Identity in the House of Ilorin (2009), African Discourse in Islam, Oral Traditions, and Performance (2010), and Cultural Globalization And Plurality: Africa and the New World (2011).